Effect of acid/alkali shifting on function, gelation properties, and microstructure of Mesona chinensis polysaccharide-whey protein isolate gels. (August 2021) - Jiang, Lian; Ren, Yanming; Shen, Mingyue; Zhang, Jiahui; Yu, Qiang; Chen, Yi; Zhang, Haide; Xie, Jianhua
Abstract: This paper investigates the potential of composite gels, formed by the pH-treated whey protein isolation (WPI) and Mesona chinensis polysaccharides (MCP) solutions, as jelly processing ingredients. The functional, gelation properties, and microstructure of MCP-WPI gels were investigated under specific conditions (pH 4–10). The results showed that MCP and WPI can form a stable gel under the condition of pH 10, ζ-potential increased and the particle size decreased with the increase of pH. The water-holding capacity (WHC) of MCP-WPI gels was the lowest at pH 6 and the highest at pH 10. Rheological results showed that the apparent viscosity, storage modulus ( G′ ), and loss modulus ( G″ ) of MCP-WPI gels increased with the increase of pH. At pH 10, MCP-WPI gels had the highest creep/recovery ability. The gel strength and rupture stress of MCP-WPI gels increased significantly ( P  < 0.05) with the pH. The more uniform structure and finer water pores were observed with scanning electron microscope (SEM) and confocal laser scanning microscopy (CLSM) in higher pH conditions (pH 8 and 10), and more disordered and coarse gel networks were formed at pH 4 and pH 6. These results indicated that higher pH promoted MCP-WPI gel formation, which provided a reference for the innovation of heat-induced gel material in the medical and food industries. Graphical abstract: Image 1 Highlights: Apparent viscosity and viscoelasticity of MCP-WPI gels increased with pH. MCP-WPI gels had high creep recovery ability and water holding capacity at pH 10. With pH increased, the rupture stress of MCP-WPI gels increased. The more uniform structure and fine water pores in MCP-WPI gels at high pH.